2013
DOI: 10.1063/1.4775768
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependent carrier dynamics in telecommunication band InAs quantum dots and dashes grown on InP substrates

Abstract: Correlations between the morphology and emission properties of trench defects in InGaN/GaN quantum wells J. Appl. Phys. 113, 073505 (2013) Optical characterization of free electron concentration in heteroepitaxial InN layers using Fourier transform infrared spectroscopy and a 2×2 transfer-matrix algebra J. Appl. Phys. 113, 073502 (2013) Influence of structural anisotropy to anisotropic electron mobility in a-plane InN Appl. Phys. Lett. 102, 061904 (2013) Sub-250nm light emission and optical gain in Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 66 publications
1
18
0
Order By: Relevance
“…InAs dashes on InP can emit light in the telecommunication window around 1.55 μm which, combined with unique properties of artificialatom-like structures, very high surface density, broad gain function, and nearly instantaneous gain response, all providing extraordinary spectral tunability and high-speed modulation, makes them favorable as an active medium in lasers and optical amplifiers [9][10][11][12]. The laser-related properties of the QDash ensemble have already been extensively investigated and many details have been understood and reported, as for instance the influence of the growth parameters on the nanostructure geometry, QDash ensemble homogeneity and emission energy, as well as the electronic structure [9,[13][14][15]. In addition, polarization properties of emission along with the spatial character and strength of the quantum confinement have also been studied [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…InAs dashes on InP can emit light in the telecommunication window around 1.55 μm which, combined with unique properties of artificialatom-like structures, very high surface density, broad gain function, and nearly instantaneous gain response, all providing extraordinary spectral tunability and high-speed modulation, makes them favorable as an active medium in lasers and optical amplifiers [9][10][11][12]. The laser-related properties of the QDash ensemble have already been extensively investigated and many details have been understood and reported, as for instance the influence of the growth parameters on the nanostructure geometry, QDash ensemble homogeneity and emission energy, as well as the electronic structure [9,[13][14][15]. In addition, polarization properties of emission along with the spatial character and strength of the quantum confinement have also been studied [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…I 0 is the luminescence intensity in the case of 100% efficiency. Normal radiative lifetime in InAs QDs remains almost constant in the low-temperature range studied in this work, 23 and we set s À1 rad;U ¼ s À1 rad;L s À1 rad . Since electrons very close to the electron Fermi level are condensed in the SC density of states (DOS) based on the Bardeen Cooper Schrieffer (BCS) theory, 24 this assumption is rationalized in the present highly n-type doped sample.…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, a hybrid system comprising gold-magnetite nanoparticles was used to remotely measure (GNP) and increase (CFNP) the temperature in the range of 15 to 40°C, with accuracy of 0.5°C [25]. Alternatively, it has been reported that nanosized semiconductor structures also display a monotonic redshift of the optical emission energy (E) as the temperature (T) increases [134]. This behaviour is usually described by the empirical Varshni equation [135]:…”
Section: Remote Nanoparticle-based Nanothermometersmentioning
confidence: 99%